Factors influencing self-management behaviors in persons with lupus nephritis: A cross-sectional study - Hanrop, Sirikarn; Sriyuktasuth, Aurawamon; Pongthavornkamol, Kanaungnit; Piaseu, Noppawan; Chawanasuntorapoj, Ratana (Belitung Raya Publisher - Belitung Raya Foundation, 2024)
Background: Patients with lupus nephritis experience disease symptoms and side effects from treatment. Although self-management behaviors are important in patients with this disease, there is limited research on the factors influencing these behaviors. Objective: This study aimed to examine the factors influencing self-management behaviors in patients with lupus nephritis. Methods: This cross-sectional study was conducted in 240 patients with lupus nephritis at a university hospital in Thailand between August 2019 and December 2020 using a random sampling method. Data were collected using a demographic and clinical characteristic questionnaire, Self-Management Behavior Questionnaire, Self-efficacy for Managing Chronic Disease: A 6-item Scale, Knowledge about Lupus Nephritis Questionnaire, Family Support Scale, Social Networks in Adult Life Questionnaire, and Memorial Symptom Assessment Scale for Lupus Nephritis. Descriptive statistics and multiple linear regression analyses were employed. Results: The participants reported a moderate level of self-management behaviors. Multiple regression analyses revealed that disease duration, income, symptoms, self-efficacy, knowledge, family support, social networks, and classes of lupus nephritis significantly explained 21% of the variance in self-management behaviors (R2 = 0.21; F(8,231) = 7.73; p <0.001). Family support (β = 0.32, p <0.001) and symptoms (β = −0.23, p<0.001) were significant determinants of self-management behaviors in patients with lupus nephritis. Conclusion: The findings provide valuable insight for nurses to better understand the factors influencing self-management behaviors in patients with lupus nephritis. Patients with low family support and high symptom severity may face difficulty in performing self-management behaviors. Nurses should pay more attention to these patients and provide family-based interventions to optimize self-management behaviors in this population.